Nocardia Septic Arthritis of the Knee Following Repeated Intra-Articular Injections in a Diabetic Patient with Osteoarthritis: A Case Report (Pulse, 2025)
Background: Septic arthritis in diabetic patients with advanced osteoarthritis poses diagnostic and therapeutic challenges. Nocardiosis, a rare opportunistic infection caused by soil-borne Nocardia species, typically affects the lungs, brain, or skin and carries a high mortality rate of up to 40%. Although joint involvement is uncommon, it is increasingly reported, particularly in immunocompromised individuals. Diabetes and prior intra-articular corticosteroid injections are notable risk factors. Timely recognition of such atypical pathogens is critical for effective management. Case Presentation: A 57-year-old woman with poorly controlled type 2 diabetes mellitus and radiographic evidence of grade 4 knee osteoarthritis presented with signs of chronic septic arthritis following multiple intra-articular steroid injections. Despite empirical treatment with broad-spectrum antibiotics, her symptoms persisted. Initial workup, including a multiplex PCR test. Definitive identification of Nocardia was achieved via direct microscopic examination of synovial fluid, which revealed Gram-positive, branching, partially acid-fast filaments on Gram staining and modified Ziehl-Neelsen staining. Subsequent culture confirmed the presence of Nocardia species. The patient underwent urgent surgical drainage followed by targeted antimicrobial therapy, resulting complete clinical recovery. Conclusion: This case underscores the need for heightened clinical suspicion of atypical organisms like Nocardia in cases of refractory septic arthritis, particularly in immuno-compromised patients or those with a history of intra-articular injections. Comprehensive microbiological evaluation including classical staining techniques and culture can be instrumental in guiding diagnosis and improving patient outcomesPulse Vol.17, 2025 P: 44-47